Genetic Etiology in Nonsyndromic Mandibular Prognathism. Issue 1 (January 2017) - Liu, Hanghang; Wu, Chenzhou; Lin, Jie; Shao, Jun; Chen, Qianming; Luo, En
Abstract : Abstract: Mandibular prognathism (MP) is considered to be a cranial-facial disorder resulting from the interaction between genes and environment. Recent studies have demonstrated that susceptible chromosomal regions and candidate genes may be responsible for MP. In this study, the authors present current views on the effect of genetic components in nonsystematic mandibular prognathism, in order to clarify the genetic etiology of MP. Data source were Electronic databases, manual searching, and reference lists checking, up to April 2016. Study selection, level of evidence assessment, and data extraction were done by 2 individuals in duplicate. Ninety-one studies were retrieved in initial electronic and manual search, and based on the established inclusion and exclusion criteria, 15 were selected for the review. In result, loci 1p36, 1q32.2, 1p22.3, 4p16.1, 6q25, 19p13, 14q24.3, 14q31.1, and 14q31.2 were thought to harbor genes that confer susceptibility to MP. Genes Matrilin-1, ADAMTS1, COL2A1, and EPB41 seemed to be strongly associated with MP while gene of growth hormone receptor was in dispute. Genetic components appeared to be associated with MP. However, in view of the variety of populations and results in related publications, further studies are necessary to clarify the genetic etiology of MP.